MASCDB, a database of images, descriptors and microphysical properties of individual snowflakes in free fall - Jacopo Grazioli; Gionata Ghiggi; Anne-Claire Billault-Roux; Alexis Berne (Scientific Data, 2022)
Measurement(s) fall speed • snowfall images • snow crystals • geometrical characteristics • textural characteristics • snowfall microphysics Technology Type(s) multi angle snowflake camera